Implementation of Fluorescent in situ hybridization (FISH) as a method for detecting microdeletion syndromes - our first experiences - Sukarova-Angelovska E.; Piperkova K.; Sredovska A.; Ilieva G.; Kocova M. (Macedonian Academy of Sciences and Arts, 2007)
Fluorescent in situ hybridisation (FISH) is a complementary cytogenetic method which has an important role in discovering unsolved cases of mental retardation and multiple anomalies. The ability of this method to detect complex and cryptic chromosomal rearrangements exceeds the resolution of the usual cytogenetic banding techniques; therefore it has a wide implementation in modern cytogenetic laboratories - in routine work, as well as for research purposes. We analysed 19 patients with microdeletion syndromes - 9 patients with Williams syndrome, 4 patients with Prader-Willi syndrome, and 6 patients with DiGeorge syndrome. On the basis of evaluation of facial dysmorphism and the presence of specific major anomalies, all the patients met the criteria for the diagnosis of the syndrome. FISH studies were performed, confirming the suspected syndrome in patients.
Воведување на флуоресцентната in situ хибридизација (FISH) како метод за детектирање на микроделециони синдроми - наши први искуства